Clonal Diversity of Meticillin-Resistant Staphylococcus aureus Isolated From Intensive Care Unit. Issue 3 (May 2015) - Javidnia, Sara; Talebi, Malihe; Katouli, Mohammad; Shojaie, Ali; Lari, Abdolaziz Rastegar; Pourshafie, Mohammad R.
Abstract : Background: This study was performed to examine the clonal diversity of meticillin-resistant Staphylococcus aureus isolated from intensive care units (ICUs) from 3 hospitals located in Tehran, Iran. Methods: A total of 67 S. aureus were obtained from ICU and were subjected to antimicrobial susceptibility tests and pulsed-field gel electrophoresis typing. Results: Twenty (30%) of the isolates were resistant to oxacillin with the minimum inhibitory concentrations greater than or equal to 256 μg/mL for 18 of them. Pulsed-field gel electrophoresis analysis showed 4 common clonal and 3 single types in 3 hospitals. Conclusions: The presence of common clonal groups in ICU wards among the 2 hospitals is indicative of the persistence and dissemination of certain meticillin-resistant S. aureus strains within the hospitals.